Pengaruh Penambahan Tepung Kacang Merah Terhadap Mutu Organoleptik, Fisik Dan Kimia Nugget Ayam Kampung - Nurina Rahmawati; Andri Cahya Irawan (Universitas Islam Kadiri, 2021)
This research aims to observe the effect of addition of red peanutlevel on organoleptic quality, physical quality dan chemical quality of domestic chicken nugget.The research was done by completely randomized design with 4 treatment and 6replications. P1 (domestic chicken meat + 5% red peanut flour), P2 (domestic chicken meat + 10% red peanut flour), P3 (domestic chicken meat + 15% red peanut flour) and P4 (domestic chicken meat + 20% red peanut flour). The variables measured include: organoleptic quality, physical quality and chemical quality.The result showed that, the addition of red peanut flour 20% was very significantly affected (P<0.01) to smell and flavor of domestic chicken nugget with score 2.60, the addition of red peanut flour 20% was very significantly affected (P<0.01) to WHC and protein level of domestic chicken nugget with each value 54.73%; 20.01%. The addition of red peanut flour 5% was very significantly affected (P<0.01) to water content of domestic chicken nugget 50.69%. It can be concluded that the best treatment of addition of red peanut flour 20% to smell, flavour, WHC and protein level of domestic chicken nugget.